Risk factors for recurrent Pelvic Inflammatory Disease. (January 2020) - Safrai, Myriam; Rottenstreich, Amihai; Shushan, Asher; Gilad, Ronit; Benshushan, Avi; Levin, Gabriel
Abstract: Objective: Pelvic inflammatory disease (PID) is a common infection which can result in severe long term morbidity, such as chronic pelvic pain and infertility. The morbidity increases in correlation to the number of PID events. Our study aim to assess the risk factors for recurrence of pelvic inflammatory disease. Methods: A retrospective case control study was conducted using data for all women who were admitted to a tertiary medical center for a recurrent PID over a duration of 15 years. Women who had a recurrent PID were compared to women admitted for PID treatment without further recurrence. Forward stepwise multivariate logistic regression analysis was subsequently carried out. Results: The study included 133 women of whom 33 had recurrent PID. Women in the recurrent PID group had a higher rate of previous pelvic surgery (12 (36 %) vs. 20 (20 %), adjusted odds ratio [OR] 2.2 (95 % confidence interval CI 1.06–5.4, p = 0.05) and more had intrauterine devices (IUD) still in place if they had been previously present (5 (71.4 %) vs. 9(25.7 %), OR 7.2, (95 % CI 1.18–43.9), p = 0.02). The majority were treated with a combination of Ampicillin and Gentamycin, fewer received Augmentin or a cephalosporin base regimen (28 (84.8 %) vs 56 (56.0 %), OR 4.4, (95 % CI 1.5–12.3, p = 0.02), (1 (3.0 %) vs 27 (27.0 %), OR 0.08, (95 % CI 0.01-0.64), (4 (12.2 %) vs 17 (17.0 %)) respectively. In addition, invasive treatment had been required in more patients who later had a recurrent PID (6 (18.1 %) vs. 4(4.0 %), OR 5.3 (95 % CI 1.1.4-20.2), p = 0.007). Antibiotic regimens and invasive treatment were independently associated with recurrent PID (OR 2.69; 95 % CI 1.13–6.41, OR 2.10; 95 % CI 1.19–3.71, respectively). Conclusion: Among women with PID, special awareness should be given to women with previous pelvic surgery, who required an additional interventional treatment and have an IUD inserted. Efforts should be made to achieve treatment success and optimal prevention to prevent recurrent PID.